MENGENAL SEJARAH PANDE BESI TRADISIONAL - Ari Supriyanto (Ornamen, 2011)
BlacksmithÂ was the term for someone who has a knack for making a variety of objects made of iron. The term blacksmith so much as mentioned in some inscriptions of ancient Javanese as the pande / pandai wsi. Blacksmith at present have a marginal position, was very helpful in providing a variety of metal objects that are useful for the general public. Expertise and skills passed down from generation to generation to make this group survived until today. Skills that are descendants raises the question: how the lives of their predecessors in the past? Therefore, this short article to trace back to the past to search for information in connection with the blacksmith